Defective hippocampal neurogenesis underlies cognitive impairment by carotid stenosis-induced cerebral hypoperfusion in mice - Fraga, Enrique; Medina, Violeta; Cuartero, María Isabel; García-Culebras, Alicia; Bravo-Ferrer, Isabel; Hernández-Jiménez, Macarena; Garcia-Segura, Juan Manuel; Hurtado, Olivia; Pradillo, Jesus Miguel; Lizasoain, Ignacio; Moro, María Ángeles (Frontiers in Cellular Neuroscience, 2023)
Chronic cerebral hypoperfusion due to carotid artery stenosis is a major cause of vascular cognitive impairment and dementia (VCID). Bilateral carotid artery stenosis (BCAS) in rodents is a well-established model of VCID where most studies have focused on white matter pathology and subsequent cognitive deficit. Therefore, our aim was to study the implication of adult hippocampal neurogenesis in hypoperfusion-induced VCID in mice, and its relationship with cognitive hippocampal deficits. Mice were subjected to BCAS; 1 and 3 months later, hippocampal memory and neurogenesis/cell death were assessed, respectively, by the novel object location (NOL) and spontaneous alternation performance (SAP) tests and by immunohistology. Hypoperfusion was assessed by arterial spin labelling-magnetic resonance imaging (ASL-MRI). Hypoperfused mice displayed spatial memory deficits with decreased NOL recognition index. Along with the cognitive deficit, a reduced number of newborn neurons and their aberrant morphology indicated a remarkable impairment of the hippocampal neurogenesis. Both increased cell death in the subgranular zone (SGZ) and reduced neuroblast proliferation rate may account for newborn neurons number reduction. Our data demonstrate quantitative and qualitative impairment of adult hippocampal neurogenesis disturbances associated with cerebral hypoperfusion-cognitive deficits in mice. These findings pave the way for novel diagnostic and therapeutic targets for VCID.